1978
DOI: 10.1002/ar.1091910407
|View full text |Cite
|
Sign up to set email alerts
|

Circadian variation in cell division of the mouse alimentary tract, bone marrow and corneal epithelium

Abstract: Circadian rhythms in DNA synthesis are described for the tongue epithelium, five different regions of the alimentary canal (gut)--esophagus, stomach, duodenum, jejunum and rectum--and bone marrow in a group of BDF1 male mice. A circadian rhythm is also described for the mitotic index in the corneal epithelium in the same mice. The data document for the first time in the same animals the dramatic variation in cell division encountered from one region of the gut to another. This variation is seen in the amplitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(58 citation statements)
references
References 11 publications
5
52
0
Order By: Relevance
“…These data suggest that it may be possible for the cell-cycle rhythm to be entrained to 24-h fluctuations in temperature in a rhythmic host environment. Discussion DNA synthesis, mitosis, and the expression of cell-cycle proteins in mammalian tissues (e.g., skin, bone marrow, gut, tongue, and oral mucosa) occur with a 24-h cycle in vivo (3)(4)(5)(49)(50)(51)(52)(53)(54)(55) and circadian periodicity of cell mitosis persists in rodents in constant darkness (2,5). Daily rhythms of cell-cycle protein expression (Cyclins E, A, and B1) were also observed in human oral epithelium sampled by biopsy at 4-h intervals for 24 h from healthy human subjects (3).…”
Section: Resultsmentioning
confidence: 99%
“…These data suggest that it may be possible for the cell-cycle rhythm to be entrained to 24-h fluctuations in temperature in a rhythmic host environment. Discussion DNA synthesis, mitosis, and the expression of cell-cycle proteins in mammalian tissues (e.g., skin, bone marrow, gut, tongue, and oral mucosa) occur with a 24-h cycle in vivo (3)(4)(5)(49)(50)(51)(52)(53)(54)(55) and circadian periodicity of cell mitosis persists in rodents in constant darkness (2,5). Daily rhythms of cell-cycle protein expression (Cyclins E, A, and B1) were also observed in human oral epithelium sampled by biopsy at 4-h intervals for 24 h from healthy human subjects (3).…”
Section: Resultsmentioning
confidence: 99%
“…Cellular proliferation is organized within proliferating tissues throughout each day (1)(2)(3)(4). In the usually quiescent liver, regeneration following partial hepatectomy results in tight circadian gating of cell division at specific times of day (5).…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggested an S-phase acrophase in early afternoon. Scheving et al (30) showed, in rodent gut, significant circadian variation in [3H] TdR incorporation in mucosal epithelia throughout the entire gastrointestinal tract. Although the phasing of the rhythms in different regions of the gastrointestinal tract was fairly similar, the acrophase for tongue epithelium preceded that of colonic epithelium by about 3 hours.…”
Section: Discussionmentioning
confidence: 99%